2013
DOI: 10.1186/1479-5876-11-109
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition in calcium nephrolithiasis

Abstract: Idiopathic calcium nephrolithiasis is a multifactorial disease with a complex pathogenesis due to genetic and environmental factors. The importance of social and health effects of nephrolithiasis is further highlighted by the strong tendency to relapse of the disease. Long-term prospective studies show a peak of disease recurrence within 2–3 years since onset, 40-50% of patients have a recurrence after 5 years and more than 50-60% after 10 years. International nutritional studies demonstrated that nutritional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…Some other studies have also observed that the excretion of calcium is increased with high consumption of cooking salt. [ 22 23 ] An increase of about 6 g (100 mmol) of NaCl produces an increase of calciuria of 40 mg (1 mmol) in normal adults and 80 mg (2 mmol) in hypercalciuric patients leading to formation of kidney stones. These findings corroborate those obtained from the present study on the respective determinants (calcium and sodium intake vis-à -vis renal stone formation).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some other studies have also observed that the excretion of calcium is increased with high consumption of cooking salt. [ 22 23 ] An increase of about 6 g (100 mmol) of NaCl produces an increase of calciuria of 40 mg (1 mmol) in normal adults and 80 mg (2 mmol) in hypercalciuric patients leading to formation of kidney stones. These findings corroborate those obtained from the present study on the respective determinants (calcium and sodium intake vis-à -vis renal stone formation).…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of lifestyle patterns by various studies in affluent countries such as the United States and Northern European countries has shown that how the increased prevalence of stones occurred simultaneously with the increased sedentary lifestyle. [ 23 ]…”
Section: Discussionmentioning
confidence: 99%
“…This nutrient, in fact, promotes the proliferation of lymphocytes, with a consequent increase in the generation of antibodies [ 79 , 85 , 92 ]. It is well known that infections increase oxidative stress and usually activate phagocytes that release ROS, so vitamin C is a well-known antioxidant that can counteract these effects by increasing phagocytosis and ROS generation and improving microbial killing [ 92 94 ]. Furthermore, supplementation with vitamin C appears to be able to prevent and treat respiratory and systemic infections [ 92 ].…”
Section: Immunonutrition: the Role Of Specific Nutrients And Microbiomentioning
confidence: 99%
“…Despite the occurrence of abnormal urinary bladder contents and their importance for animal health and performance, many aspects of the epidemiology and pathogenesis in pigs have not yet been fully investigated. Dietary and environmental factors play an important role in the development of uroliths, since diet influences the urine composition and pH (Dogliotti et al, ; Grases, Costa‐Bauza, & Prieto, ; Kienzle, ; Parivar, Low, & Stoller, ). Sufficient water supply and consumption will also decrease the concentration of urinary solutes and increase their solubility (Moe, ).…”
Section: Introductionmentioning
confidence: 99%